Exploring the need for a well-being assessment checklist for asnaf in agricultural entrepreneurship programmes - Mohd Aris, Noorfazreen; Habidin, Nurul Fadly; Muhammad, Fidlizan (Universiti Teknologi MARA Selangor, 2026)
This study aims to examine the need for developing a well-being assessment checklist for asnaf (eligible zakat recipients) involved in zakat-based agricultural entrepreneurship programmes from the perspectives of experts and programme implementers. Adopting a qualitative research design, data were collected through in-depth interviews with informants comprising specialists in zakat, social well- being, and practitioners directly involved in agricultural entrepreneurship initiatives. Thematic analysis was employed to identify key needs underpinning the development of a more comprehensive assessment instrument. The findings indicate that the evaluation of asnaf well-being is currently not supported by systematic, structured, and multidimensional instruments. Strong consensus emerged on the necessity of a comprehensive checklist incorporating multidimensional indicators, including support and resources, quality of life aligned with maqasid shariah, economic and spiritual well-being, entrepreneurial competencies, future planning, and independence. Informants further highlighted the operational value of such a checklist in enhancing monitoring, transparency, accountability and evidence-based decision- making within zakat institutions. Overall, this study provides empirical support for the development of a context-specific and practical well- being assessment checklist, with important implications for strengthening the effectiveness of productive zakat programmes aimed at improving the holistic well-being of asnaf.